Mitigating climate disruption in time: A self-consistent approach for avoiding both near-term and long-term global warming - Dreyfus, Gabrielle B.; Xu, Yangyang; Shindell, Drew T.; Zaelke, Durwood; Ramanathan, Veerabhadran (Proceedings of the National Academy of Sciences - PNAS, 2022)
The ongoing and projected impacts from human-induced climate change highlight the need for mitigation approaches to limit warming in both the near term (< 2050) and the long term (> 2050). We clarify the role of non-CO₂ greenhouse gases and aerosols in the context of near-term and long-term climate mitigation, as well as the net effect of decarbonization strategies targeting fossil fuel (FF) phaseout by 2050. Relying on Intergovernmental Panel on Climate Change radiative forcing, we show that the net historical (2019 to 1750) radiative forcing effect of CO₂ and non-CO₂ climate forcers emitted by FF sources plus the CO₂ emitted by land-use changes is comparable to the net from non-CO₂ climate forcers emitted by non-FF sources. We find that mitigation measures that target only decarbonization are essential for strong long-term cooling but can result in weak near-term warming (due to unmasking the cooling effect of coemitted aerosols) and lead to temperatures exceeding 2 °C before 2050. In contrast, pairing decarbonization with additional mitigation measures targeting short-lived climate pollutants and N₂O, slows the rate of warming a decade or two earlier than decarbonization alone and avoids the 2 °C threshold altogether. These non-CO₂ targeted measures when combined with decarbonization can provide net cooling by 2030 and reduce the rate of warming from 2030 to 2050 by about 50%, roughly half of which comes from methane, significantly larger than decarbonization alone over this time frame. Our analysis demonstrates the need for a comprehensive CO₂ and targeted non-CO₂ mitigation approach to address both the near-term and long-term impacts of climate disruption.